Evolutionary dynamics do not lead to correlated equilibria - Yannick Viossat (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
In (Viossat, 2006, The replicator dynamics does not lead to correlated equilibria, forthcoming in Games and Economic Behavior), it was shown that the replicator dynamics may eliminate all pure strategies used in correlated equilibrium, so that only strategies that do not take part in any correlated equilibrium remain. Here, we generalize this result by showing that it holds for an open set of games, and for many other dynamics, including the best-response dynamics, the Brown-von Neumann-Nash dynamics and any monotonic or weakly sign-preserving dynamics satisfying some standard regularity conditions. For the replicator dynamics and the best-response dynamics, elimination of all strategies used in correlated equilibrium is shown to be robust to the addition of mixed strategies as new pure strategies.
Keywords: C72; C73; 330; Correlated equilibrium; evolutionary dynamics; survival; as-if rationality; Spieltheorie; Gleichgewichtstheorie